2004
DOI: 10.1111/j.1365-2699.2004.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of a fine‐scale breeding bird atlas using a geographical information system and partial canonical correspondence analysis: environmental and spatial effects

Abstract: Aim To assess the relative roles of environment and space in driving bird species distribution and to identify relevant drivers of bird assemblage composition, in the case of a fine-scale bird atlas data set. LocationThe study was carried out in southern Belgium using grid cells of 1 · 1 km, based on the distribution maps of the Oiseaux nicheurs de Famenne: Atlas de Lesse et Lomme which contains abundance for 103 bird species.Methods Species found in < 10% or > 90% of the atlas cells were omitted from the bird… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 39 publications
2
48
0
5
Order By: Relevance
“…We first compared bacterial community composition shifts between all wells and found that although the majority of the variation could be explained by spatial and environmental variables, a portion of the variance remained unexplained. Other ecological studies that used variance partitioning have also observed high levels of unexplained variation (Titeux et al, 2004). When we examined the bacterial community composition between the bioreduction wells only, the unexplained variation decreased.…”
Section: Engineering Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first compared bacterial community composition shifts between all wells and found that although the majority of the variation could be explained by spatial and environmental variables, a portion of the variance remained unexplained. Other ecological studies that used variance partitioning have also observed high levels of unexplained variation (Titeux et al, 2004). When we examined the bacterial community composition between the bioreduction wells only, the unexplained variation decreased.…”
Section: Engineering Controlsmentioning
confidence: 99%
“…When we examined the bacterial community composition between the bioreduction wells only, the unexplained variation decreased. Titeux et al (2004) suggested that the high unexplained species assemblages could be because of unaccounted factors such as the fluctuations of communities along temporal and spatial scales, unmeasured environmental variables and limitations in separating geographical factors that could be because of spatially structured processes. Our results suggested that other geochemical variables could be important indicators, and while it is difficult to measure everything, future efforts should attempt to include a range of variables to represent an even more holistic approach.…”
Section: Engineering Controlsmentioning
confidence: 99%
“…Notably, spatially explicit phenomena must be considered in terms of scale and experimental design, so as not to overestimate the influence of horizontal space in a community. Similarly, the proportion of the variation in the species matrix that could not be explained by the available environmental variables does not affect the significance of the species-environment relationships (Brack & Smilauer 1998), and such "noise" is common in vegetation data, due in part to the fact that not all favorable sites are occupied by their respective species (Titeux et al 2004).…”
Section: Relationships Between Species and Spatial-environmental Varimentioning
confidence: 99%
“…We ran two separate RDA analyses for each variable, one without and one with control for spatial position of the sites (Legendre, 1993). For the latter, we first defined a minimum adequate model describing the geographic position of the reserves by defining a model with latitude (lat), longitude (long), their second-degree polynomials, and all possible combinations (e.g., lat + long, lat · lat + long 2 …) (Titeux et al, 2004), and then simplified this model using the CANOCO forward selection procedure. The selected covariate model, y ~ lat + long + lat · long, was used in all spatially controlled analyses.…”
Section: Analysesmentioning
confidence: 99%